HUKUM KARMA DIPANDANG DARI SEGI ETIKA - S. Reksosusilo (Litbang STFT Widya Sasana Malang, 2001)
Karma is a law that sprung from the Hindu tradition centuries ago. Nevertheless, it is still actual; and as a law it can be useful to cope the present challenge of evil made by human conducts in the paradigm of “jungle law.” I believe that the karma law can even lead positively society to the moral and civilized one. Civil society of Indonesia needs the karma law. This article is my personal attempt to underline the important role of the karma law in building up Indonesian civil society especially in terms of lawful enforcement to prevent evil occurred daily. The theme shall be dealt with in the following scheme: 1) the karma law in Hinduism, 2) ethics of human conducts, 3) conscience and ethical reasoning, 4) the karma law and ethics, 5) some coclusive points